2008
DOI: 10.1590/s1415-52732008000700009
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre fatores socioeconômicos e insegurança alimentar: estudo de base populacional na Região Metropolitana do Rio de Janeiro, Brasil

Abstract: Estimar a prevalência de insegurança alimentar em famílias de Duque de Caxias, município localizado na Região Metropolitana do Rio de Janeiro, e avaliar a associação entre indicadores socioeconômicos e insegurança alimentar. 1 Este estudo faz parte do projeto "Avaliação do estado nutricional, hábitos alimentares e insegurança alimentar no município de Duque de Caxias, Rio de Janeiro: desenvolvimento de um instrumento simplificado para avaliação de consumo alimentar saudável". Apoio financeiro: Ministério da Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0
77

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 8 publications
5
25
0
77
Order By: Relevance
“…In the population of Popular Restaurants workers from Rio de Janeiro, the prevalence of foodinsecure households was almost twice of that found by PNAD 2009 (30.2%). Salles-Costa et al 15 studied families from the district Campos Elíseos in Duque de Caxias, considered one of the poorest districts of Rio de Janeiro, and found a prevalence of food insecurity of 53.8%, similar to that found herein. In two municipalities characterized by low human development indices in the states of Pernambuco and Paraíba, household food insecurity prevalences reached almost 90.0% 16 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the population of Popular Restaurants workers from Rio de Janeiro, the prevalence of foodinsecure households was almost twice of that found by PNAD 2009 (30.2%). Salles-Costa et al 15 studied families from the district Campos Elíseos in Duque de Caxias, considered one of the poorest districts of Rio de Janeiro, and found a prevalence of food insecurity of 53.8%, similar to that found herein. In two municipalities characterized by low human development indices in the states of Pernambuco and Paraíba, household food insecurity prevalences reached almost 90.0% 16 .…”
Section: Discussionsupporting
confidence: 80%
“…Salles-Costa et al 15 found that the education level of the family head was also significantly associated with food insecurity. In the ecological study conducted by Foley et al 23 in South Australia with 19,037 individuals, a significant association was also found between low education level and food insecurity (p<0.01).…”
Section: Discussionmentioning
confidence: 99%
“…This result was expected because food insecurity is intrinsically related to income, since FI scales measure the level of food restriction quantitatively and qualitatively, especially caused by income limitation 25,26 . Educational level results show a similar pattern, considering that educational level is a proxy for income 18 .…”
Section: Discussionmentioning
confidence: 84%
“…A significância das diferenças (p < 0,05) entre as frequências encontradas foi verificada por meio do teste Qui-quadrado. 35 de oito estudos [15][16][17]19,35,[39][40][41] ) e o abastecimento de água no domicílio (um 39 de nove estudos [15][16][17]19,26,35,[39][40][41] ) foram outras variáveis que, também, mostraram-se associadas, nas análises bivariadas, à insegurança alimentar familiar.…”
Section: Métodosunclassified